PERUBAHAN TRADISI JAWA” (Studi Tentang Upacara Adat Pelaksanaan Perkawinan Suku Jawa Di Kepenghuluan Harapan Makmur Kecamatan Bagan Sinembah Raya Kabupaten Rokan Hilir) - Azhari, Yusuf Azis; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Research on the Implementation Ceremony Javanese in Kepenghuluan Harapan Makmur Rokan Hilir. This research was conducted with the aim to explain how changes in the Java Tribe pelksanaa marriage and what factors cause these changes. In this study the author uses qualitative research which is an attempt to present the social world, and perspective in life, in terms of concept, behavior, perception, and the question of human examined. Data collection techniques using purposive sampling method, where the subject is determined by the researchers itself, which consists of key informants 2, informants consist of 5 people. The data collection technique using observation, interview and documentation. The research proves that indeed there is a change at some stage events are held such as: the preparation phase before the wedding, the implementation phase which formerly carried out in detail, but now people prefer to carry out the events that are considered important. This is influenced by several factors such as the times are increasingly changing, the economic factor is the cost factor associated with the lineage of tribal and environmental factors a person's residence.Keywords: Implementation, marriage ceremony, Javanese